2016
DOI: 10.4236/ojn.2016.67059
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Perinatal Asphyxia in Newborns Delivered at Term

Abstract: Perinatal asphyxia is defined as harm to the fetus or the newborn caused by hypoxia and/or ischemia of various organs with intensity to produce biochemical and/or functional changes. Understanding the risk factors for this clinical condition allows the identification of vulnerable groups, enabling an improvement in care planning in the perinatal period in neonatal intensive care units. In this sense, this research aimed to identify risk factors for perinatal asphyxia present in newborns term that showed record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
6
7
0
2
Order By: Relevance
“…Similar results were also expressed through the results using the observational study method which said that of 184 infants who experienced perinatal death, it was found that 13.04% of perinatal deaths were caused by asphyxia neonatorum. Asphyxia also accounted for 34% of perinatal deaths compared to those without asphyxia neonatorum [6]. This is in line with the research which stated that there was a significant relationship between asphyxia and neonatal death, namely infants with asphyxia will be 7.85 times more likely to experience neonatal death compared to those without asphyxia.…”
Section: The Risk Of Asphyxia To Perinatal Deathsupporting
confidence: 85%
“…Similar results were also expressed through the results using the observational study method which said that of 184 infants who experienced perinatal death, it was found that 13.04% of perinatal deaths were caused by asphyxia neonatorum. Asphyxia also accounted for 34% of perinatal deaths compared to those without asphyxia neonatorum [6]. This is in line with the research which stated that there was a significant relationship between asphyxia and neonatal death, namely infants with asphyxia will be 7.85 times more likely to experience neonatal death compared to those without asphyxia.…”
Section: The Risk Of Asphyxia To Perinatal Deathsupporting
confidence: 85%
“…The mortality rate of the sample, as well as the percentage of children presenting neurological sequelae was lower than that reported by other studies. Surveys have indicated a rate of mortality and permanent neurological sequelae as well superior to our findings 11,23,24 .…”
Section: Resultssupporting
confidence: 50%
“…This finding is in line with study conducted in Brazil which examined prevalence of prenatal asphyxia in a reference maternity. 8 This study also reveal that neonate delivered by using C/S and instruments were 3.23 and 3.06 times more likely develop birth asphyxia as compared with vaginal delivery. This find confront with study in which the perinatal asphyxia had more frequently in vaginal deliveries.…”
Section: Discussionsupporting
confidence: 52%
“…The finding is concurrent with study conducted in Brazil on risk factor associated with asphyxia. 8 Neonate who was born with gestational age of < 37week and > 42 week were 3.81 and 6.667 time more likely develop birth asphyxia as compared to neonate with gestational age within 37-42 week. Neonates who were born with cord presentation was 4.135 more likely develops birth asphyxia as with non-cord presentation.…”
Section: Discussionmentioning
confidence: 92%